Orchestration of Proper Piano Pieces as a Self-Interpretation - STRONKO, Boryslav (Studia Universitatis Babes-Bolyai Musica, 2023)
The study is focused on the problem of composers’ self-interpretation in the orchestrations of their own piano pieces. This specific case of a creative re-thinking contains not only adaptation of a piano score to orchestral instruments, but also adding new semantic meaning, sound atmosphere and texture principles as well as further development of initial music idea. For the analysis two pieces of Maurice Ravel and Borys Lyatoshinsky – two prominent masters of orchestration and piano miniature of 20th century, were chosen. Their approaches are distinguishably different: (a) the detailed reordering of the initial idea from an “instrument Piano” to an “instrument Orchestra” (Ravel); (b) throughout development with essential changes firstly within piano means, than by orchestral means in the genre of Symphony (Lyatoshinsky).